In-Situ X-Ray Absorption Spectroscopic Studies of Ions at Oxide-Water Interfaces - Gordon E. Brown Jr.; George A. Parks; Catherine J. Chisholm-Brause (CHIMIA)
Instructive insight is gained from a novel application of synchrotron-based EXAFS spectroscopy to the study of metal complexes sorbed at oxide/water interfaces. Fluorescence-yield X-ray absorption measurements were made on high surface area, wet oxide samples with less than monolayer sorbate coverages using high intensity synchrotron radiation. The samples studied included Co2⊕(aq) on γ-Al2O3 and TiO2 (rutile), Pb2⊕(aq) on γ-Al2O3, and aqueous selenate and selenite ions on α-FeOOH (goethite). Direct, in-situ measurements of the average distances, numbers, and identities of first- and second-neighbors surrounding the sorbed atoms in these samples were derived from the experimental data. – The results for Co2⊕ on γ-Al2O3 and TiO2, at pH 6.8, indicate that Co2⊕ forms inner-sphere complexes, that it does not sorb as a three-dimensional precipitate or diffuse into the oxide, and that it forms multi-nuclear complexes on γ-Al2O3 but smaller polymers or monomeric complexes on TiO2. – Results for Co2⊕ on γ-Al2O3 provide the first, direct structural evidence for multi-nuclear metal sorption complexes on an oxide surface. These results also indicate that the nature of the oxide surface influences the type of adsorption complex formed. - The sorption complexes formed by Pb2⊕ on γ-Al2O3 at pH 6.0 are similar; Pb2⊕ probably forms dimeric or a combination of monomeric and small multi-nuclear complexes. – Selenate is sorbed as an outer-sphere complex (pH 3.5) and selenite is sorbed as an inner-sphere, bi-dentate complex (pH 5.6) on α-FeOOH. These structural results provide the first molecular-level explanation for the weak binding of selenate and the strong binding of selenite at the goethite/water interface.